2022
DOI: 10.1590/1678-7757-2022-0144
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rd inhibits migration and invasion of tongue cancer cells through H19/miR-675-5p/CDH1 axis

Abstract: Objective: Tongue squamous cell carcinoma (TSCC) is an oral cancer, with high malignancy and frequent early migration and invasion. Only a few drugs can treat tongue cancer. Ginsenoside Rd is a ginseng extract with anti-cancer effects. Many noncoding RNAs are abnormally expressed in tongue cancer, thus influencing its occurrence and development. H19 and miR-675-5p can promote cancer cell growth. This study aimed to analyze the regulation effect of ginsenoside Rd on H19 and miR-675-5p in tongue cancer.Methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It has been reported that GS-Rd can inhibit the proliferation of human cervical cancer cell HeLa cells by regulating the expression of Bcl-2/Bax, regulating mitochondrial transmembrane potential, activating the expression of caspase family members, and inhibiting the proliferation of human cervical cancer cell HeLa cells through apoptosis [ 38 ]. In recent years, it has been reported that GS-Rd can effectively inhibit the activity of various tumor cells such as tongue cancer, gastric cancer, breast cancer, and colorectal cancer [ 12 , [39] , [40] , [41] ]. Research on tongue cancer has also found that Ginsenoside Rd inhibits migration and invasion of tongue cancer cells through the H19/miR-675-5p/CDH1 axis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GS-Rd can inhibit the proliferation of human cervical cancer cell HeLa cells by regulating the expression of Bcl-2/Bax, regulating mitochondrial transmembrane potential, activating the expression of caspase family members, and inhibiting the proliferation of human cervical cancer cell HeLa cells through apoptosis [ 38 ]. In recent years, it has been reported that GS-Rd can effectively inhibit the activity of various tumor cells such as tongue cancer, gastric cancer, breast cancer, and colorectal cancer [ 12 , [39] , [40] , [41] ]. Research on tongue cancer has also found that Ginsenoside Rd inhibits migration and invasion of tongue cancer cells through the H19/miR-675-5p/CDH1 axis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different LncRNAs exert distinct roles, influencing the advancement of TSCC in various aspects such as cell migration, autophagy, apoptosis, proliferation, invasion, and cellular drug resistance, through diverse signaling pathways [ 3 , 25 , 26 , 27 ]. A study suggested that knocking out LncRNA CASC9 in TSCC cells SCC15 and CAL27 significantly promotes autophagy and apoptosis while inhibiting proliferation [ [28] , [29] ]. Furthermore, the application of certain drugs can target these LncRNAs to curb the growth of TSCC(3).…”
Section: Introductionmentioning
confidence: 99%
“…Tongue cancer is the most common type of cancer. The most common treatment for tongue cancer is mainly surgical, but after surgery, it greatly affects patients' functions such as chewing, speech and swallowing, and the prognosis is poor, so the search for an effective antitongue cancer drug has become a hot research topic (Tang et al, 2020;Chang et al, 2022;Elseragy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%